A label-free fluorescent biosensor based on a catalyzed hairpin assembly for HIV DNA and lead detection. Issue 21 (11th May 2021) - Xiong, Yu; Dai, Jianyuan; Zhang, Yujiao; Zhou, Cuisong; Yuan, Hongyan; Xiao, Dan
Abstract : Herein, a label-free fluorescent signal amplification system based on a catalyzed hairpin assembly (CHA) is reported. Abstract : Herein, a label-free fluorescent signal amplification system based on a catalyzed hairpin assembly (CHA) is reported. In this system, two hairpin probes, H1 and H2, were well-designed in which G-quadruplex sequences were integrated into H2. The CHA reaction was triggered by target/trigger DNA and G-quadruplex sequences were released, which can bind the fluorescent amyloid dye thioflavin T (ThT) to provide fluorescence signals. At the same time, target/trigger DNA was released from the product of the CHA reaction (H1–H2), which continued to initiate the next CHA cycle, and the signal was eventually amplified. This signal amplification approach has been successfully used to develop a label-free fluorescent sensing platform for sensitive detection of human immunodeficiency virus (HIV) DNA and Pb 2+ .